2001
DOI: 10.1114/1.1349703
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Blood Flow Patterns in the Human Right Coronary Artery

Abstract: Evidence suggests that atherogenesis is linked to local hemodynamic factors such as wall shear stress. We investigated the velocity and wall shear stress patterns within a human right coronary artery (RCA), an important site of atherosclerotic lesion development. Emphasis was placed on evaluating the effect of flow waveform and inlet flow velocity profile on the hemodynamics in the proximal, medial, and distal arterial regions. Using the finite-element method, velocity and wall shear stress patterns in a rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
132
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(154 citation statements)
references
References 40 publications
17
132
1
2
Order By: Relevance
“…In most cases, regions of low wall shear stress predominate at the proximal end of the artery with further areas of low wall shear stress decreasing in size and frequency as the artery is traversed. This is in agreement with results presented by Kirpalani et al (Kirpalani et al, 1999) and Myers et al (Myers et al, 2001). The reason for this is probably related to the fact that most of the arteries taper towards the distal end.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In most cases, regions of low wall shear stress predominate at the proximal end of the artery with further areas of low wall shear stress decreasing in size and frequency as the artery is traversed. This is in agreement with results presented by Kirpalani et al (Kirpalani et al, 1999) and Myers et al (Myers et al, 2001). The reason for this is probably related to the fact that most of the arteries taper towards the distal end.…”
Section: Discussionsupporting
confidence: 94%
“…The wall shear stress patterns differ most significantly when the flow is either slow or reversing, which is perhaps not surprising. This is in agreement with experimental observations (Asakura and Karino, 1990) as well as previous simulations which suggest that cycle averaged wall shear stress patterns are in good agreement with steady flow patters (Myers et al, 2001;van de Vosse et al, 2001;Feldman et al, 2002). Simulations presented here suggest that this is a reasonable approximation for about 70% of the cardiac cycle, ie from t = 0.30 to t = 1.00, ignoring the slight bumps around t = 0.43 and t = 0.63.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 in the baseline case for example). It was further contended that both these haemodynamic metrics are affected more by variation in three-dimensional vessel geometry (geometric factors such as curvature of the vessel) among patients [66][67][68], which is the main objective of this work and a planned future study. In addition, using the subject's own flow waveform over a non-specific (generalized) waveform leads to more accurate results [58].…”
Section: Predicting the Vascular Deposition Of Nanoparticles In The Smentioning
confidence: 99%
“…Ascribing greater precedence to errors in geometry than errors in specifying the inflow conditions appears to be justified for initial work such as this. For example, the study of flow in a human right coronary artery of Meyers et al [16] found the inflow conditions to be of secondary importance to the geometry. As the flow must respond both to continuous changes in geometry, and to viscous diffusion from the wall, inflow effects are bound to diminish with distance so that finding is not unexpected.…”
Section: Introductionmentioning
confidence: 99%